Prevalence and Associated Factors of Burnout among Medical and Dental Students at University of Science and Technology, Sana'a, Yemen, 2024 - Mohammed, Ameer Dhalnon; Habtoor, Ahmed Nasser; Al-Arashi, Ahmed Mohammed; Al-Humi, Islam Adel; Al Qadasi, Ibraheem Sadeq; Al-Saadi, Mohammed Abdullah (My University, 2024)
Background: Incisional hernia (IH) is one of the most common postoperative complications following abdominal surgery. Studies identifying the prevalence rate and associated factors of IH are scarce regionally and locally in Yemen. Objectives: To identify the prevalence rate and associated factors of Incisional Hernia among patients of University of Science and Technology Hospital from 2020 to 2023 in Sana'a, Yemen, 2024.